THE ANALYSIS OF CONTENT TEXTS IN THE TEXTBOOK: COMMUNICATIVE ENGLISH IN CONTEXT PUBLISHED BY GRAFINDO: TINJAUAN ISI TEKS DALAM BUKU TEKS: COMMUNICATIVE ENGLISH IN CONTEXT YANG DITERBITKAN OLEH GRAFINDO - Sitoresmi, Woro Endah; Herlini, Herlini; Asma, Nur (BASIS (Bahasa dan Sastra Inggris), 2023)
Since the analysis of textbook is highly important and beneficial for teaching and learning process and also as a reflective syllabus and curriculum, the present study aims to overview the content texts in the English textbook: Communicative English in Context for ninth graders published by Grafindo. It involves kinds of texts, how they were presented in this English textbook and their compatibility with syllabus and 2013 curriculum. It belongs to descriptive qualitative study which used document analysis to proceed the data in this study which kinds of texts become the main data. The findings show that kinds of texts which also embedded grammar points in this textbook are in the form of dialogues and informative texts such as descriptive, procedural, report and narrative texts which have fulfilled social function, generic structure and linguistic feature. Furthermore, these texts which become the materials for teaching and learning process are simply designed and compatible with syllabus and 2013 curriculum since they are relevant with students’ competencies.